Decoding the cyberbullying behaviour research trends: A bibliometric analysis. - Ishak, Noor Syazwani; Roslan, Mohd Firdaus; Abdullah, Khairul Hafezad; Abd Razak, Mohd Ridwan; Mohaidin, Abdul Muhaimin (Journal of Islamic, Social, Economics and Development, 2024)
Cyberbullying behaviour is a form of bullying that takes place online or through electronic devices which may disturb the peace of users and others. This study aims to explore cyberbullying behaviour research-related publishing patterns and rank the most used author keywords in the Scopus and Web of Science (WoS) databases. The eminent software, ScientoPy and VOSviewer, are used to run and execute relevant publication data retrieved from Scopus and WoS. The results showed a positive trend in the growth of cyberbullying behaviour literature in both databases since 2012. The top three research areas that dominate this topic are “psychology”, “education & educational research”, and “computer science”. Based on the country analysis, United States has become an active publisher, followed by Spain and United Kingdom. Importantly, this study emphasised the scholarly communication practices prevalent in cyberbullying behaviour research have impressively propagated. The trends will assist researchers in recognising the various fields in identifying the core areas, proactive institutions, and productive authors published in this knowledge for supplementary investigation. Besides, by examining the most popular keywords, the results of this study enable researchers to discover the possibility for future research that may be conducted, particularly concerning the annual growth rates, which have been trending in the last five years.